Implications Law Islam On Child Marriage In Minors Due To In Doti For The Society Tanah Towa Village, Kajang District Bulukumba District: Implications Law Islam On Child Marriage In Minors Due To In Doti For The Society Tanah Towa Village, Kajang District Bulukumba District - Meilani; Achmad Musyahid; Misbahuddin (Jurnal Diskursus Islam, 2026)
This thesis examines the implications of Islamic law on underage marriage caused by doti among the people of Tanah Towa Village, Kajang District, Bulukumba Regency. It addresses three main questions: (1) the consequences of child marriage due to doti, (2) community perceptions of such practices, and (3) the implications of Islamic law on underage marriage resulting from doti. This study employs field research with theological-normative and juridical approaches. Data sources include primary, secondary, and tertiary data, collected through observation, interviews, documentation, and literature review. Data analysis is conducted through data reduction, presentation, and conclusion drawing. The findings show that, first, the practice of underage marriage due to doti is generally similar to marriage practices in the Kajang community. Second, community perceptions vary: while many consider it a common cultural practice, others view it as inappropriate because it violates human rights, particularly children’s right to education. Third, from the perspective of Islamic law, although such marriages may be considered legally valid, they violate regulations on minimum marriage age and contradict fundamental principles of marriage in Islam, especially those related to consent, welfare, and protection. This study implies that underage marriage driven by doti limits children’s opportunities and personal development. Therefore, parents and society should allow children greater autonomy in determining their future and be more aware of the negative consequences of forced or premature marriage.